2019
DOI: 10.1017/cjn.2019.76
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Collegiate Student-Athletes’ Concussion-Related Knowledge and Behaviors

Abstract: ABSTRACT:Objective:This study aimed to explore student-athletes’ concussion-related knowledge and attitudes toward reporting symptoms, demographic predictors of knowledge and attitudes, and determine whether responses to the survey changed following an online educational intervention.Methods:A total of 108 Division I student-athletes enrolled at a large southern university completed a survey evaluating knowledge regarding concussion-related terminology, symptoms and recovery trajectories, as well as attitudes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 36 publications
1
11
1
Order By: Relevance
“…Concussion knowledge has been heavily studied and surveyed in the United States, and much of the literature pertaining to collegiate athletes suggested that their concussion knowledge and ability to identify true symptoms of concussion, such as headache, sensitivity to light or noise, feeling dizzy, and balance difficulty, were moderate. 30 Comparatively, the Irish collegiate athletes in our study had the poorest scores in total concussion knowledge and symptom recognition. These results parallel the findings of previous researchers 19,21 who observed that Gaelic games athletes and Irish jockeys possessed a good overall understanding of concussion but had misconceptions about false signs and symptoms of concussion.…”
Section: O N L I N E F I R S Tmentioning
confidence: 54%
“…Concussion knowledge has been heavily studied and surveyed in the United States, and much of the literature pertaining to collegiate athletes suggested that their concussion knowledge and ability to identify true symptoms of concussion, such as headache, sensitivity to light or noise, feeling dizzy, and balance difficulty, were moderate. 30 Comparatively, the Irish collegiate athletes in our study had the poorest scores in total concussion knowledge and symptom recognition. These results parallel the findings of previous researchers 19,21 who observed that Gaelic games athletes and Irish jockeys possessed a good overall understanding of concussion but had misconceptions about false signs and symptoms of concussion.…”
Section: O N L I N E F I R S Tmentioning
confidence: 54%
“…Reporting the symptoms of suspected concussions depends on athletes' ability to recognize and attribute their symptoms, as many common symptoms are subjective (e.g., headache and dizziness). Several studies on knowledge of concussion have been conducted among collegiate athletes outside of Japan (Fedor and Gunstad, 2015;Beidler et al, 2018Beidler et al, , 2021Chapman et al, 2018;Bernstein et al, 2019;Anderson et al, 2021). These studies have investigated athletes' perceptions of symptoms based on the suspected concussion symptoms presented in the consensus statement (McCrory et al, 2017) and the Sports Concussion Assessment Tool 5 (SCAT 5) (Echemendia et al, 2017) while adding dummy symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Sex differences in concussion reporting is currently inconclusive in the current literature; some research suggests there may be no differences, 15,16 and some studies suggest there are difference. 17,18 For example, Sullivan et al suggests males are more likely to hide concussions. 17 Concussion reporting patterns can also differ between sports with differing levels of contact and sport-specific culture, but these results are inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…To assess this, we performed a cross-sectional study in elementary and high school and collegiate student athletes and compared responses to a series of standardized vignettes that asked if they would report a possible concussive head injury during various scenarios and to list reasons why they would be unlikely to report. Prior concussions and level of competition were a priori decided to be potential confounders, 18 hence all analyses were controlled for concussion history and highest level of competition. We hypothesized there would be differences in concussion reporting behaviors between sports of different levels of contact and no differences between the sexes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation